Agentes microbiológicos productores de infecciones y su resistencia bacteriana, en pacientes de la Unidad de Cuidados Intensivos del Hospial General Isidro Ayora Loja - Pérez Carrión, Ximena Alejandra (2019)
Bacterial resistance and the rapidity with which it develops, has been one of the main causes of morbidity, mortality, and hospital stay in public health. Therefore, the present cross-sectional retrospective study has been conducted, aimed at knowing the etiology and pattern of bacterial resistance present in patients admitted to the Intensive Care Service of the General Hospital Isidro Ayora de Loja, 2017, this study was developed with a sample of 134 crops, in which was obtained: Klebsiella Pneumoniae in a 22% for the Masculine gender, and Escherichia Coli in 20% for the Feminine gender. Patients older than 65 years accounted for 36% of the crops, with Klebsiella Pneumoniae in 21% of the samples. In the type of sample, it was found that in Blood, Staphylococcus Coagulase Negative represented 21%, in Urine Escherichia Coli 41%, in tracheal secretion and other samples Klebsiella Pneumoniae accounted for 21% and 33% respectively. The microorganisms showed greater resistance to Cephalosporins in 31%, the intermediate resistance and sensitivity was for the Aminoglycosides in 32% and 22% respectively. Klebsiella Pneumoniae showed resistance in 15.7% of Penicillins, 23.5% of Aminoglycosides, 37.4% of Antibiotics Combined with Betalactamase Inhibitors, 18.3% of Carbapenems, 47% of Cephalosporins and 13% of Quinolones. Therefore, it was concluded that Klebsiella Pneumoniae is the microorganism that have the highest frequency and resistance in the Intensive Care Unit. Key words: Klebsiella pneumoniae, antibiotics, resistance, crops.